The Legal Concept “Family Members of the Ownerof Residential Premises” - T. P. Strogonova (Сибирское юридическое обозрение, 2019)
In this article the questions of subject structure of family members are considered, the main legal signs of family members of the owner are revealed and their contents are opened. The Author argues that if the owner has made a legally significant action to move a person into his dwelling as a family member (without reference to commercial hiring or gratuitous use), there is recognition by the owner of this fact, regardless of their mutual legal status (kinship, properties, etc.). Although it is advisable to create a rule that directly indicates how the corresponding will of the owner or his authorized representative should be issued.